Psychology of the Game in the Works by L. Panteleev about Childhood (Proceedings of Southern Federal University. Philology, 2020)
The article focuses on the game, which becomes one of the plot components of L. Panteleev’s works and helps to reveal the inner world of the characters-children more deeply. Special attention is paid to the time of the analyzed works, which reflects the days of peace («Honest word»), as well as the era of wars and revolutions («Chief engineer», «Lenʹka Panteleev», «Republic SHKID»), which helps to trace the link between historical time and the game of children, which is perceived by them as a true reality or conditionally.Key words: game, fantasy, test, conventionality, children’s space, adult space.DOI 10.18522/1995-0640-2020-1-132-137